(untitled) (Research, Society and Development, 2022)
Introduction: Medicine graduation, by usually prioritizing the technical knowledge to the detriment of the humanistic ones, provides the formation of “robotic” professionals, who also show lower levels of professionalism. Therefore, medical arts education emerges as an alternative to humanize clinical practice. Objective: To conduct an integrative literature survey regarding the use of art in the development of medical professionalism during undergraduate education. Methods: Study in integrative review format. After using the descriptors and applying the inclusion and exclusion criteria, ten studies from the Virtual Health Library (BVS) and the National Library of Medicine of the United States of America (PubMed) databases and from the Google Scholar platform were selected and analyzed. Results: The analyzed studies showed that many skills that are important for clinical practice can be acquired by studying arts, such as: observation, empathy, cultural sensitivity, teamwork, communication, critical thinking, attention, clinical reasoning, and active listening. Conclusion: The contact with arts during medical graduation proved to be beneficial for the development of professionalism.